Pharmacology, prevalence in Germany, and analytical data of cyclobutylmethyl‐ and norbornylmethyl‐type synthetic cannabinoid receptor agonists. Issue 4 (9th January 2023) - Pulver, Benedikt; Riedel, Jan; Schönberger, Torsten; Halter, Sebastian; Lucas, Tobias; Opatz, Till; Grafinger, Katharina Elisabeth; Scheu, Martin; Zschiesche, Annette; Pütz, Michael; Pützer, Klaus; Westphal, Folker; et al.
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are distributed on the drug market to produce THC‐like effects while evading routine drug testing and legislation. The cyclobutylmethyl (CBM) and norbornylmethyl (NBM) side chain specifically circumvented the German legislation and led to the emergence of exploratory SCRAs in 2019–2021. The NBM SCRAs were detected post‐amendment of the new psychoactive substances act in 2020, which scheduled all CBM SCRAs. All six SCRAs are full agonists at the cannabinoid receptor 1 compared with Δ 9 ‐tetrahydrocannabinol and CP‐55, 940. The CBM SCRAs showed binding affinities of Ki : 29.4–0.65 nm and potencies of EC50 : 483–40.1 nm (CBMICA << CBMINACA < CBMeGaClone). The norbornyl derivatives exhibited high affinities (Ki : 1.87–0.25 nm ), with indazole being the most affine. Functional activity data confirmed that the indazole derivative tends to be the most potent of all three NBM SCRAs (EC50 : 169–1.78 nm ). The sterically demanding NBM side chain increased the affinity and activity of almost all core structures. Future studies should be conducted on similarly voluminous side chain moieties. The 'life cycle' of all SCRAs on the drug market was less than a year. Notably, Cumyl‐CBMICA was the most prevalent while also having the weakest cannabimimetic properties. Quantification of Cumyl‐CBMICA during peak consumption in late 2019 and early 2020 revealed an increase in the concentration on the herbal material, which, together with forum entries and blog posts, corroborates the low in vitro cannabimimetic properties. Seizure prevalence data indicate that almost all SCRAs continue to be identified in 2022, potentially due to remaining stocks. Abstract : Six exploratory SCRAs with CBM and NBM side chains circumvented the German NpSG 2019–2021 with Cumyl‐CBMICA the most prevalent. Potency and affinity at the CB1 receptor are sensitive to changes in the core (indole << indazole < γ‐carbolinone) and the side chain (CBM << NBM). The sterically demanding NBM side chain increased the affinity and activity for almost all core structures.